2012
DOI: 10.15605/jafes.027.01.19
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Toxic Multinodular Goiter with Anaplastic Carcinoma

Abstract: This report concerns a 71-year-old female with long standing untreated toxic multinodular goiter (TMG) coexisting with anaplastic thyroid carcinoma who presented with progressive shortness of breath and easy fatigability. Thyroid function tests showed suppressed TSH and elevated FT4 and FT3. Anti-thyroid hormone drugs were started. Thyrotropin receptor antibody was negative. A thyroid scan revealed both hot and cold nodules and fine needle aspiration biopsy (FNAB) of the thyroid gland showed colloid nodule. Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Despite these advanced tumours, very rarely was mortality directly due to thyroid cancer 1 8. This, however, excludes concurrent hyperthyroidism and anaplastic thyroid cancer in which distant metastasis and mortality were uniformly manifested 12 13 24 25. Statistical analysis showed that no demographic or clinical factor was associated with aggressiveness of the well-differentiated cancers.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Despite these advanced tumours, very rarely was mortality directly due to thyroid cancer 1 8. This, however, excludes concurrent hyperthyroidism and anaplastic thyroid cancer in which distant metastasis and mortality were uniformly manifested 12 13 24 25. Statistical analysis showed that no demographic or clinical factor was associated with aggressiveness of the well-differentiated cancers.…”
Section: Discussionmentioning
confidence: 96%
“…In some cases, cancer was suspected preoperatively owing to the presence of cervical lymphadenopathy, suspicious ultrasound findings or fine needle aspiration biopsy results 1 8. Still fewer are patients whose hyperthyroidism was discovered during evaluation for clinically suspicious or preoperatively diagnosed thyroid cancer 12 13. In these two patients, features of malignancy with metastasis to the lymph nodes, bone and lungs were more prominent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation